A REVIEW ON BIG DATA ANALYTICS FOR RETAIL INDUSTRY AT CHINA - Haidong Zhang; Zailani Abdullah (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Big data analytics (BDA) methodologies and tools are used extensively for retailing at China. However, the existing insights are scattered over different literature sources and there is a lack of a structured and unbiased review methodology to systematise BDA application areas in the retail at China comprehensively covering efficiency, resilience and sustainability paradigms. In this study, we first propose a systematic review methodology for the field of BDA in retailing. Second, we use the methodology proposed for a systematic literature review on BDA techniques in the retailing fields aiming at classifying the existing BDA models/techniques employed, structuring their practical application areas, identifying the research gaps and potential future research directions. Our analysis is triangulated across efficiency, resilience, and sustainability perspectives. The developed review methodology and proposed novel classifications and categorisations can be used by researchers and practitioners alike for a structured analysis and applications of BDA in retailing at China.